2020
DOI: 10.1016/j.fuel.2019.116085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bio-crude components derived from pyrolysis of soft wood and its esterified product by ultrahigh resolution mass spectrometry and spectroscopic techniques

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 46 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…A detailed information of the pyrolytic and esterification conditions can be found elsewhere. 23 The crude bio-oil was subjected to esterification/acetalization with n -butanol in the presence of H 2 SO 4 /dehydration to produce an upgraded product. Hereafter referred to as the “esterified bio-oil,” this upgraded product results from the combined esterification of carboxylic acids to esters and acetalization of aldehydes and ketones into acetals.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed information of the pyrolytic and esterification conditions can be found elsewhere. 23 The crude bio-oil was subjected to esterification/acetalization with n -butanol in the presence of H 2 SO 4 /dehydration to produce an upgraded product. Hereafter referred to as the “esterified bio-oil,” this upgraded product results from the combined esterification of carboxylic acids to esters and acetalization of aldehydes and ketones into acetals.…”
Section: Methodsmentioning
confidence: 99%
“…A crude pyrolysis bio-oil sample with humidity less than 10 wt % was produced using a mixture of softwoods as original material . The samples were dissolved in acetone at a final concentration of 3 ppm, and 1 μL was injected into a 30 m DB-5 column (0.25 mmID, 0.25 μm).…”
Section: Methodsmentioning
confidence: 99%
“…ESI is prone to ionize compounds with low DBE but more oxygen atoms. In a recent work, Palacio-Lozanoa et al reported the characterization of bio-crudes by using FT-ICR MS with (±)­ESI and APPI ionization sources and combined with the NMR analysis.…”
Section: Characterization Of Alternative Fuelsmentioning
confidence: 99%